Effect of different torque settings selected during instrumentation on fracture strength of endodontically treated teeth - Demet Altunbaş; Eda Gürsu (Selçuk University, 2022)
Background: The study evaluated the effect of root canal instrumentation at low and high torque settings on the fracture strength of endodontically treated teeth. Methods: Ninety extracted single-rooted human mandibular incisors were randomly divided into one control (CG) and two experimental groups (n=30): no instrumentation or filling (CG), instrumentation with ProTaper Universal files at low torque settings, and instrumentation with ProTaper Universal files at high torque settings. Root canal filling was performed with an epoxy resin-based sealer and gutta-percha using a single-cone technique in the experimental groups. Each specimen was tested for fracture strength. The analysis of variance and Tukey test were used to analyze the obtained data. The significance level was set at 0.05. Results: Statistically significant differences were observed between the groups (p = 0.001). While the difference between the CG and low torque groups was not significant (p > 0.05), the difference between the CG and high torque, low and high torque groups was significant (p < 0.05). Conclusion: According to this study results, since the lowest fracture strength value was observed in the high torque group, clinicians may be advised to choose the lowest torque settings recommended by the manufacturers for rotary systems.